Networkcube: Bringing Dynamic Network Visualizations to Domain Scientists - Bach, Benjamin; Henry Riche, Nathalie; Fernandez, Roland; Giannisakis, Emmanoulis; Lee, Bongshin; Fekete, Jean-Daniel (2015)
Network visualizations support research in a range of scientific domains from biology to humanities. This paper presents our effort to create a platform to bridge the gap between domain scientists and visualisation researchers; NetworkCube aims in being a fast way to deploy experimental visualizations from research to domain experts analyzing dynamic networks. In turn, InfoVis researchers benefit from studying how their visualizations are used in the wild.
Posters Compendium of InfoVis 2015